1986
DOI: 10.1063/1.450586
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the one-dimensional band structures of Ni tetrabenzoporphyrin and phthalocyanine conducting polymers

Abstract: The one-dimensional band structures of (tetrabenzoporphyrinato) Ni (II) and (phthalocyaninato) Ni (II) were calculated. The reported band structures include the effects of the stacking perturbation and of the overlap between nearest neighbors. The basis functions for the intermolecular integrals were obtained from a discrete variational X-α calculation of the monomeric species. Electron spin resonance (ESR) experiments on conductive columnar stacks of these metallomacrocycles, partially oxidized with iodine, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…It should be mentioned that the unit cells of most of the recently characterized organic metals or highly conducting metallomacrocycles are rather complicated; i.e., they are beyond the present limits operative in traditional solid-state approaches. The theoretical tools applicable in this field are either based on a one-electron Hamiltonian of the Wolfsberg-Helmholtz type [15][16][17], on semiempirical SCF (self-consistent-field) HF (Hartree-Fock) approaches supplemented by ZDO (zero differential overlap) approximations [18,191, or on simplified non-self-consistent X , scattered wave techniques [20]. These computational methods allowed for investigations of 1D solids with unit cells containing up to 35 atoms.…”
Section: Ram~rez and Bohmmentioning
confidence: 99%
“…It should be mentioned that the unit cells of most of the recently characterized organic metals or highly conducting metallomacrocycles are rather complicated; i.e., they are beyond the present limits operative in traditional solid-state approaches. The theoretical tools applicable in this field are either based on a one-electron Hamiltonian of the Wolfsberg-Helmholtz type [15][16][17], on semiempirical SCF (self-consistent-field) HF (Hartree-Fock) approaches supplemented by ZDO (zero differential overlap) approximations [18,191, or on simplified non-self-consistent X , scattered wave techniques [20]. These computational methods allowed for investigations of 1D solids with unit cells containing up to 35 atoms.…”
Section: Ram~rez and Bohmmentioning
confidence: 99%
“…4,[7][8][9] Charge transport measurements and bandstructure calculations on one-dimensional stacks of metallo-porphyrins and phthalocyanines, including H 2 , Ni, and Zn complexes, have indicated that the interaction of the π orbitals from the porphyrin ligand with the metal d x 2 −y 2 orbital can play a significant role in intramolecular orbital formation and intermolecular charge transport along the one-dimensional stack and in bulk crystals. [28][29][30][31] Ishikawa, for example, found by calculation and solution absorption spectroscopy that linear stacks of closed-shell phthalocyanines could be treated as metalfree phthalocyanines. 29 Comparatively, whereas conduction in one-dimensional stacks of NiPc has been suggested to result solely from ligand orbitals, 59 conduction in one-dimensional NiTBP has been shown to involve both the ligand π orbitals and the metal d orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the solid state, experimental and theoretical studies on the electronic structure and conduction pathways in linearlystacked metallo-porphyrins and phthalocyanines showed intramolecular charge transport is dependent upon molecular spacing, and inter-stack charge transport dependent on molecular composition. [28][29][30][31] The prevalence of copper phthalocyanine (CuPc) in OFETs has led to it being studied by ab initio calculations both in the single-molecule and solid forms. [32][33][34][35] Noguchi et al calculated the crystal growth characteristics of solid TBP, reporting that TBP crystallized along the b axis a) Electronic mail: pshea@umich.edu; http://www.eecs.umich.edu/omelab parallel to the substrate plane.…”
Section: Introductionmentioning
confidence: 99%
“…Note, in calculating the matrix elements between Bloch states, only the effects of neighboring segments are included. Full details of this supercell method can be found elsewhere [9].…”
Section: Approachmentioning
confidence: 99%